2008
DOI: 10.1111/j.1478-3231.2008.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Sialoadenectomy enhances hepatic injury induced by lipopolysaccharide/galactosamine in mice

Abstract: Our results suggest that the effect of sialoadenectomy on LPS/GalN-induced liver toxicity may be the consequence of an altered cytokine production by the liver and a reduced CS release from adrenal glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Differential expression of keratins of tongue coating might be closely related to the changes in functional substances caused by hepatitis B disease. Epidermal growth factor (EGF) in saliva was overexpressed,42, 43 while liver injury which might be caused by hepatitis B disease 24. The increased level of EGF might be associated with the differential expression of keratins in tongue coating.…”
Section: Resultsmentioning
confidence: 99%
“…Differential expression of keratins of tongue coating might be closely related to the changes in functional substances caused by hepatitis B disease. Epidermal growth factor (EGF) in saliva was overexpressed,42, 43 while liver injury which might be caused by hepatitis B disease 24. The increased level of EGF might be associated with the differential expression of keratins in tongue coating.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that sialoadenectomy induces mild liver injury in young mice [5,56] and that this results in increased sensitivity to the hepatotoxic effect of bacterial lipopolysaccharides [49]. Several stressors also induce mild liver injury in young adult mice [13,48], and it is known that stress exacerbates the damaging effect of several toxins [7,41,43].…”
Section: Consequences On Life Spanmentioning
confidence: 98%
“…This leads to a reduction in the number of remaining hepatocytes, accompanied by an increase in their size [5]. These alterations render the liver more sensitive to bacterial toxins [49].…”
Section: Introductionmentioning
confidence: 99%
“…Host hormones also play important roles in liver diseases (110–113). Females are generally considered to be more susceptible to alcohol‐induced liver injury than males.…”
Section: Crosstalk With Other Physiological and Pathophysiological Mementioning
confidence: 99%